Clinical study of mild hypothermia therapy after endovascular mechanical thrombectomy for acute anterior circulation massive cerebral infarction. - ZHANG Jia-qi; LIU Yang; SHI Yi; REN Zhi-qiang; HAN Bing-sha; FENG Guang (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To explore the efficacy and safety of mild hypothermia therapy in patients with acute anterior circulation massive cerebral infarction after endovascular mechanical thrombectomy. Methods Eighty - two patients with acute anterior circulation massive cerebral infarction admitted to He'nan Provincial People's Hospital from January 2023 to August 2024, who underwent mechanical thrombectomy, were included. Hypothermia group (n = 41) received mild hypothermia therapy with a target core temperature of 33-34 °C for 48-72 h immediately after surgery, and the others didn't (mechanical thrombectomy group, n = 41). Serum neuron - specific enolase (NSE) levels were measured 72 h after operation; prognosis was assessed using the modified Rankin Scale (mRS) at 3 months after discharge, and good prognosis and morbidity and mortality rates were recorded; as well as the complication rates were recorded during hospitalization after surgery. Univariate and multivariate Logistic regression analyses were used to screen for factors influencing prognosis after mechanical thrombectomy in patients with acute anterior circulation massive cerebral infarction. Results The serum NSE level at 72 h after operation in the hypothermia group was lower than the mechanical thrombectomy group [18.86 (13.35, 30.54) pg/L vs. 21.43 (18.30, 32.90) pg/L; Z = -2.147, P = 0.032], and the good prognosis rate at 3 months after discharge was higher than the mechanical thrombectomy group [46.34% (19/41) vs. 21.95% (9/41); χ² = 5.423, P = 0.020], and the mortality rate (χ² = 0.734, P =0.391), incidence of hemorrhagic transformation (χ² = 0.497, P = 0.481), vascular reocclusion (χ² = 0.945, P = 0.331), malignant brain edema (χ² = 1.058, P = 0.304), pulmonary infection (χ² = 2.614, P = 0.106), electrolyte disturbance (χ² = 1.222, P = 0.269), arrhythmia (χ² = 0.456, P = 0.499), deep venous thrombosis (χ² = 0.311, P = 0.577), and abnormal coagulation function (χ² = 1.246, P = 0.264) during hospitalization between the 2 groups were not statistically significant. Logistic regression analysis showed that mild hypothermia was a protective factor for good prognosis after mechanical thrombectomy for acute anterior circulation massive cerebral infarction (OR = 4.457, 95%CI: 1.503-13.759; P = 0.007), while age increase (OR = 0.915, 95%CI: 0.856-0.978; P = 0.009), history of hypertension (OR = 0.175, 95%CI: 0.055-0.562; P = 0.003) were risk factors for poor prognosis. Conclusions Mild hypothermia after mechanical thrombectomy in patients with acute anterior circulation massive cerebral infarction is safe and feasible. Reducing NSE release may be one of its action pathways, and large-scale randomized controlled trials are needed to further verify its efficacy.